A Short-Term High-Fat Diet Improved the Survival of Fat Grafts in Mice by Promoting Macrophage Infiltration and Angiogenesis - Niu, Xingtang; Lai, Zhuhao; Chen, Xihang; Lu, Feng; Gao, Jianhua; Yuan, Yi (Frontiers in Cell and Developmental Biology, 2022)
Background: Adipose tissue is an ideal filler material that is widely used for soft tissue defects. But the low survival rate and complications associated with such grafts pose a serious challenge, which limits their clinical application. Adipose tissue is a metabolic diet-responsive tissue; however, the influence of diets on fat grafting remains ambiguous. Methods: We extracted inguinal fat pads from C57/BL6 male mice, and transplanted them into the dorsal region of recipient mice (0.3 mL). Post-fat-grafting, mice (n = 54) were randomized into three groups, namely normal diet (ND), high carbohydrate diet (HC), and high-fat diet (HF). Structural changes were assessed by histological staining. Lipolysis activity and vascular regeneration of grafts on day 30 were analyzed using real-time polymerase chain reaction, immunofluorescence, and western blotting. Results: The grafts of mice on HC and HF diets exhibited significantly fewer oil cysts and larger volume retention (0.18 ± 0.01, 0.21 ± 0.01, and 0.25 ± 0.01 mL, for ND, HC, and HF group, respectively, p < 0.05) on day 90. In comparison, grafts for the mice belonging to the HF groups exhibited higher expression of lipolysis-related genes, including adipose triglyceride lipase (ATGL), hormone-sensitive lipase (HSL), and carnitine palmitoyltransferase 1 (CPT1), on day 30. Furthermore, increased infiltration of macrophages (F4/80+) and the higher expression of angiogenesis genes were reported in the HF groups. Conclusion: Altogether, the administration of short-term HF diet remarkably enhanced angiogenesis and improved the quality of fat grafts, which was characterized by fewer oil cysts and higher long-term volume retention. The possible mechanisms may be due to the increased macrophage infiltration, and the promoted angiogenesis in HF grafts.